14th International Congress for Applied Mineralogy (ICAM2019) Belgorod State Technological University named after V. G. Shukhov, 23-27 September 2019, Belgorod, Russia - Glagolev, Sergey (Springer Proceedings in Earth and Environmental Sciences, 2019)
This open access proceedings of the 14th International Council for Applied Mineralogy Congress (ICAM) in Belgorod, Russia cover a wide range of topics including applied mineralogy, advanced and construction materials, ore and industrial minerals, mineral exploration, cultural heritage, etc. It includes contributions to geometallurgy, industrial minerals, oil and gas reservoirs as well as stone artifacts and their preservation. The International Congress on Applied Mineralogy strengthens the relation between the research on applied mineralogy and the industry.